2000
DOI: 10.1017/s0958067000018406
|View full text |Cite
|
Sign up to set email alerts
|

Human muscle power generating capability during cycling at different pedalling rates

Abstract: Human locomotory performance is dependent upon the ability of skeletal muscle to generate mechanical power, and sustain that power -that is, resist fatigue. Not surprisingly the factors influencing this capability have attracted the attention of many investigators dating back to and beyond the beginning of this century (see e.g. Benedict & Cathcart, 1913;Krogh & Lindhard, 1920;Hill, 1922;Lupton, 1923;Dickenson, 1928;Wilkie, 1960Wilkie, , 1981Carnevale & Gaesser, 1991;McNaughton & Thomas, 1996). However, althou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
34
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 9 publications
8
34
0
Order By: Relevance
“…These data suggest a higher contribution of anaerobic metabolism to power production in the first 15 min at FCC + 20%. Moreover, they corroborate those of Zoladz et al (2000) who showed that beyond 100 rpm there is a decrease in external power that can be delivered at a given V0 2 with an associated earlier onset of metabolic acidosis. Importantly, this could be disadvantageous for maintained high intensity exercise.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…These data suggest a higher contribution of anaerobic metabolism to power production in the first 15 min at FCC + 20%. Moreover, they corroborate those of Zoladz et al (2000) who showed that beyond 100 rpm there is a decrease in external power that can be delivered at a given V0 2 with an associated earlier onset of metabolic acidosis. Importantly, this could be disadvantageous for maintained high intensity exercise.…”
Section: Discussionsupporting
confidence: 88%
“…The maximal power during a 10 s sprint (Zoladz et al 2000) 2. The power generating capabilities following high intensity cycling exercise close to 90% VO2max (Beelen and Sargeant 1993) the reasons behind the choice of a particular cadence during endurance cycling and the corresponding GR by cyclists remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…3) that permitted subjects to provide positive physical work (J) by applying force against the ergometer throughout the limb's extension. We anticipated that the mechanical power outputs sustained at a subject's peak rate of oxygen uptake would be similar between the experimental conditions, because mechanical power does not appear to vary substantially with limb cadence at this intensity (5,49,54). The physical consequence (Eq.…”
mentioning
confidence: 99%
“…The maximal peak power output during 10 s sprints show higher values in pedalling rates at 100 rpm and 120 rpm and are lower in cadences of 60, 80 and 140 rpm (Zoladz et al, 2000). Van Soest and Casius (2000) found in musculoskeletal modelling that best cadence to achieve short time maximum power is near 120 rpm.…”
Section: Introductionmentioning
confidence: 93%